2020
DOI: 10.1007/s00277-020-04092-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pretreatment neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios in multiple myeloma patients treated with thalidomide-based regimen

Abstract: Neutrophils to lymphocytes ratio (NLR) and platelets to lymphocytes ratio (PLR) are considered as laboratory markers of inflammation. They can be potentially useful in predicting the course of multiple neoplasms including selected hematological cancers. The aim of the study was to assess the value of NLR and PLR in predicting the effects of therapy and prognosis in multiple myeloma patients treated with thalidomide-based regimen. The study group consisted of 100 patients treated with the first line CTD (cyclop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Recently, an increasing number of studies have demonstrated the value of inflammatory response biomarkers as predictive markers for prognosis in cancers. It has been shown that the neutrophil-tolymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune inflammation index (SII) can predict the prognosis in various types of cancers (7)(8)(9). The systemic inflammation response index (SIRI) is a new systemic inflammatory response biomarker based on peripheral blood cells counts, and it was demonstrated to be effective in predicting the prognosis of esophagogastric junction adenocarcinoma (10), esophageal cancer (11) and cervical cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, an increasing number of studies have demonstrated the value of inflammatory response biomarkers as predictive markers for prognosis in cancers. It has been shown that the neutrophil-tolymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and systemic immune inflammation index (SII) can predict the prognosis in various types of cancers (7)(8)(9). The systemic inflammation response index (SIRI) is a new systemic inflammatory response biomarker based on peripheral blood cells counts, and it was demonstrated to be effective in predicting the prognosis of esophagogastric junction adenocarcinoma (10), esophageal cancer (11) and cervical cancer (12).…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al [19] reported that T lymphocyte subsets were crucial prognostic factors for newly diagnosed MM and low CD4+ T cell counts and the CD4/CD8 ratio were independent poor prognostic markers. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) also had a significant independent prognostic value for multiple myeloma patients [20]. Other routine tests, such as circulating plasma cells, renal function, normal immunoglobulins level, and serum calcium, were also considered valuable prognostic factors for newly diagnosed MM [21][22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…After removal of duplicates and browsing the titles and abstracts of the studies, 26 studies were assessed according to the inclusion and exclusion criteria. Seven other studies were subsequently excluded, and 19 retrospective studies with a total of 3818 patients published between 2013 and 2020 were finally enrolled in our meta-analysis (29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47). The process of literature screening is summarized in Figure 1.…”
Section: Study Characteristicsmentioning
confidence: 99%